The minor prophets - Farrar, Frederick William, 1831-1903 (London, UK James Nisbet)
Includes bibliographical references.
Keywords: Minor prophets, biblical characters -- Biography; Bible. O.T. Minor prophets -- criticism, interpretation, etc